2018
DOI: 10.14430/arctic4701
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sea Ice Trafficability in a Changing Arctic

Abstract: Arctic sea ice has undergone rapid changes during the last few decades, with negative implications for over-ice travel and on-ice operations, which benefit from services provided by the sea ice. A Parameter-based Trafficability Hierarchy (PATH) is presented here as a framework for developing quantitative assessment strategies that can guide planning and execution of operations on or near sea ice and quantify the impacts of recent changes on ice use. A PATH assessment has been completed for three case studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…InSAR has also been shown to reveal plausible rheologies for landfast ice (Dammert et al, 1998) and has been used to determine the origin of internal ice stresses (Berg et al, 2015). Combined with inverse modeling, InSAR enables us to determine ice deformation modes (Dammann et al, 2016), rates, and the associated stress and fracture potentials (Dammann et al, 2018b). These studies have demonstrated (1) the potential of In-SAR as a tool for assessing landfast ice dynamics and stability through local case studies and (2) its utility as a planning tool for on-ice operations (Dammann et al, 2018a, b).…”
Section: Remote Sensing Of Landfast Ice Stabilitymentioning
confidence: 99%
“…InSAR has also been shown to reveal plausible rheologies for landfast ice (Dammert et al, 1998) and has been used to determine the origin of internal ice stresses (Berg et al, 2015). Combined with inverse modeling, InSAR enables us to determine ice deformation modes (Dammann et al, 2016), rates, and the associated stress and fracture potentials (Dammann et al, 2018b). These studies have demonstrated (1) the potential of In-SAR as a tool for assessing landfast ice dynamics and stability through local case studies and (2) its utility as a planning tool for on-ice operations (Dammann et al, 2018a, b).…”
Section: Remote Sensing Of Landfast Ice Stabilitymentioning
confidence: 99%
“…Prior studies have demonstrated the utility of InSAR over landfast ice as a planning tool for on-ice operations (Dammann et al, 2018a;Dammann et al, 2018b) but we argue here that such utility and potential applications also extend to maritime activities and shipping. In regards to the latter, vessel traffic typically does not traverse landfast ice.…”
Section: Temporarily Stabilized Pack Icementioning
confidence: 76%
“…As an example, on shorter time scales, industry ice 30 roads would be able to accommodate less strain than community ice trails due to different mode of transportation and user specific needs. Further steps to identify such thresholds are outlined in Dammann et al (2018a).…”
Section: Pan-arctic Delineation Of Landfast Ice Regimesmentioning
confidence: 99%
“…Three insights emerged from the study, including: (1) tracking ice conditions along ice trails revealed clear interannual variability in the thickness of the shore-fast ice, (2) documenting trail building and hunting strategies demonstrated how the community responds to variability, and (3) developing CS information resources for the community facilitated interaction with hunters and demonstrated project relevance to environmental challenges facing the community. These insights provided a foundation for the development of a framework to quantify the impacts of loss of sea ice on safety of onice travel and operations across a range of difference icescapes and ice uses (Dammann et al 2018), which remain some of the biggest challenges for Alaska Native marine mammal hunters (Huntington et al 2017). Motivated by the need to forecast safe sea-ice conditions at operational timescales (<10 days), insights from CS-IK sea ice partnerships were included in exploring how IK fits into a forecaster toolbox to support useful sea-ice information products (Deemer et al 2018).…”
Section: Sea Ice and Oceanographymentioning
confidence: 99%